The Concept of Learning-by-Doing in the Context of Media Education and School Quality Assessment - Vrabec, Norbert; Bôtošová, Ľubica (Communication Today, 2020)
The study deals with an investigation of the results of the evaluation of the quality of Slovak secondary schools, with a speciﬁc focus on identifying differences between schools that publish a school magazine and schools that do not publish a school magazine. The research sample consisted of a total of 519 secondary schools from all parts of Slovakia, which were evaluated on the basis of 45 indicators based on data from various data sources. As a part of our research study, we worked exclusively with the most up-to-date data relating to secondary schools, obtained from the school year 2018/2019. Our study focuses on a research issue that is whether the existence of a school magazine in any way affects the results of an overall school quality assessment or not. The ﬁnal data set that we subjected to statistical testing (N = 160) consisted of 80 schools that have a magazine and 80 schools that do not have a magazine. The research hypothesis was statistically evaluated using the Pair test. We accepted the alternative hypothesis, according to which the evaluation results of schools that publish a school magazine are statistically signiﬁcantly different from schools that do not publish a school magazine. The ﬁndings of the research study point to the signiﬁcant beneﬁt of the existence of the learning-by-doing concept in school practice and point out that the experiential form of learning is effective.